STUDI IN SILICO DAN HUBUNGAN KUANTITATIF STRUKTUR TERHADAP AKTIVITAS TANAMAN MANGROVE (Avicennia marina (Forssk.) Vierh.) SEBAGAI ANTIDIABETES - Arinil Hidayati; Siswandono Siswandono; Pramudita Riwanti (Prodi Farmasi Fakultas Kedokteran Universitas Hang Tuah, 2021)
The research is applied to 20 compounds contained into Avicennia marina which is : 4',5-dihydroxy-3',5',7-trimethoxyflavone, isorhamnetin 3-O-rutinoside, quercetin, stenocarproquinone B, avicennone C, avicennone E, avicennone F, avicennone D, 4'5-dihydroxy-3',7-dimethoxyflavone, chrysoeriol 7-O-glucoside, naphta(1,2-b)furan-4,5-dione, 3-hydroxy-naphtal (1,2-b)furan-4,5-dione, kaempferol, 5-hydroxy-4',7-dimethoxyflavone, avicequinone C, 2-[2'-(2'-hydroxy)propyl]-naphta[1,2-b]furan-4,5-dione,4',5,7-trihydroxyflavone, luteolin 7-O-methylether, luteolin 7O-methylether 3'-O-beta-D-glucoside,5,7-dihidroxy-3',4',5'-trimethoxyflavone which are expected to have an effect as antidiabetics agent. It is undertaken to find out the linier or nonlinier relationship of the structure activity (QSAR), the physicochemical characters (lipophilic, electronic, and steric) to the activitychanging (rerank score). Moreover, it is also undertaken to find out which one of those 20 Avicenia marina compounds are predicted to possess the activity as the best antidiabetics agent by the comparison of pioglitazon. It is arranged through computerized methods through some progrmas such as used to make prediction of the activity by using Molegro Virtual Docker 20`11.5.0.0 from CLCBio. by using the peroxisome proliferator-activated receptor-gamma (PPAR) in code of PDB : 2XKW. The compound of isorhamnetin 3-O-rutinoside, , chrysoeriol 7-O-glucoside, dan senyawa luteolin 7-O-methylether 3'-O-beta-D-glucosdie are predicted to have the best antidiabetics agent if it is compared with comparing drug pioglitazon.